Investigating the Effect of Prosocial Voice on Psychological Empowerment of Employees - Sadeghian, Samaneh; Rahimnia, Fariborz; Shirazi, Ali; Kaffashpoor, Azar (European Journal of Sustainable Development, 2018)
The purpose of the present study is to identify the components of employee prosocial voice and the effect of staff empowerment on it in the municipality of Mashhad, the second largest city in the northeast of Iran. The research method used in this research is a mixed method. The design of the research is the exploratory mixed because firstly the qualitative method is performed and then, based on the obtained results, a quantitative method is performed. The statistical population of this research in the qualitative section is all employees of Mashhad municipality who have at least three years work experience in Mashhad municipality and have officially expressed at least 20 times their prosocial voice which according to the adequacy of sampling, people were Interviewed. The Colaizzi method was used to analyze the interviews, and as a result, the components of the prosocial voice were extracted from the staff. Then, in a quantitative section, for measuring and fitting the model, and to examine the effect of staff empowerment on it, a questionnaire was distributed among the employees who had officially experience of indicating prosocial voice. The data analysis of the quantitative part was done for answering the question and the main hypothesis of the study by confirmatory factor analysis and Amos software. The results of the confirmatory factor analysis indicated that all components of the prosocial voice were confirmed. The comparative fit index (CFI) of the model also was estimated 0.881 using the Amos software, which indicates the fitness presented of the model. The results showed that employees’ empowerment affects prosocial voice of employees. Keywords: Employee Voice, Employee Prosocial Voice, Psychological Empowerment